An endoscopic method for semi-quantitatively measuring internal pyloric diameter in healthy cats: A prospective study of 24 cases. (February 2019) - Lamoureux, Anaïs; Benchekroun, Ghita; German, Alexander J.; Freiche, Valérie
Abstract: The objectives of this study were to describe an endoscopic technique for semi-quantitative measurement of the internal pyloric diameter and apply this method to determine its typical size in a population of healthy cats. Twenty-four healthy adult cats, privately owned or originating from catteries, were prospectively recruited. Endoscopies were performed by the same investigator and cats with moderate to marked macroscopic inflammation were excluded. The internal pyloric diameter was measured with bespoke interchangeable biocompatible 'olives' (ranging from 4 to 12 mm in diameter) that could be attached to a guidewire. Attempts were made to pass the olives through the pylorus, in decreasing order of size, and the internal pyloric diameter was assumed to be equivalent to the size of the first olive that could successfully be passed. The median duration of the endoscopic procedure was <5 (interquartile range 2.7–5.4) minutes and all cats recovered quickly from the procedure without any complications. The median internal pyloric diameter in this population was 9 (interquartile range 9–10) mm, with most (23/24) cats having an internal pyloric diameter within ±1 mm of this measurement. There was no apparent effect of age, sex, breed or weight on the pyloric size. This study is the first to describe a quick and safe method for semi-quantitatively assessing the internal pyloric diameter in healthy adult cats. A prospective study is now warranted in order to determine the impact of gastrointestinal disease on pyloric diameter, for example cats with possible pyloric stenosis. Highlights: Stenosis of the pyloric canal is poorly-documented in cats. Pyloric diameter is easily measured in cats by endoscopy using olive-shaped devices. The median internal pyloric diameter in clinically healthy adult cats is 9 ± 1 mm. This technic of measurement may aid in the diagnosis of pyloric stenosis in cats.